ANALISIS PERSEPSI MASYARAKAT TERHADAP KINERJA APARATUR DESA DALAM MENINGKATKAN PELAYANAN PUBLIK DI DESA LENEK LAUK MENGGUNAKAN METODE NAIVE BAYES - Wasil, Muhammad; Mahfuz, Mahfuz (Infotek : Jurnal Informatika dan Teknologi, 2020)
Public service is an activity or series of activities in the framework of fulfilling service needs in accordance with statutory regulations for every citizen and resident of goods, services, or administrative services provided by public service providers. All types of services are provided and provided to the community by the village government apparatus, in general it has not satisfied many people. The services provided are too complicated for reasons according to the procedure, the amount of fees charged, and a very long time, so the services provided tend to be ineffective and inefficient. In this study predictions will be made about the community's satisfaction or dissatisfaction with the performance of village officials in improving services using the Naïve Bayes algorithm method. The Naive Bayes algorithm is a classification with probability and statistical methods proposed by the British scientist Thomas Bayes, which predicts future opportunities based on past experience so that it is known as Bayes theorem. This research was conducted using a data collection technique in the form of a questionnaire filled out by 50 respondents 10% of the total population, from a population of 5,539 permanent residents in the village of Lenek Lauk. Analysis of the results of the study was conducted using the Naïve Bayes algorithm method. Function to see the level of accuracy. Measurement with naïve bayes algorithm produces 92.26% accuracy and AUC value on the ROC curve is 0.924.DOI : 10.29408/jit.v3i2.2314